Biotype and insecticide resistance status of Bemisia tabaci (Gennadius) populations in Malaysia - Shadmany, Mohammad (2013)
Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is one of the most destructive pests of mainly vegetables and ornamental crops around the world. It is a cryptic species complex with at least 32 species being discovered so far. Two of the species namely B and Q are well-known invasive biotypes in this complex which upon introduction to a region can establish and partially or completely displace endemic biotypes. Both invasive biotypes are renowned for insecticide resistance potential with the Q-type being even more resistance prone than B biotype. Biotypes status of this pest in Malaysia has not been studied thoroughly and only very limited information are available thus far. Cases of poor control of this pest coupled with frequent population explosions despite application of insecticides have been reported in Malaysia in the past which can be due to high insecticide resistance development. This study aimed to reveal cryptic species status of B. tabaci in some regions of Malaysia and to evaluate insecticide resistance status of some populations against important classes of insecticides used to control them. For biotype identification, samples were collected from 10 states on different hosts and biotypes were determined using mitochondrial cytochrome oxidase subunit 1 (mtCO1) marker . In addition to the previously identified biotype for this region, Asia 1, three other biotypes namely Q, China 2, and Asia II 7 are reported for the first time in Malaysia. Biotypes other than invasive one show the genetic diversity of B. tabaci in the region. The most important finding of this study is the identification of the invasive Q biotype from Cameron Highlands, Pahang and Kundasang, Sabah. The invasive biotype can have serious negative consequences for the vegetable and ornamental production industries of the country. For insecticide resistance assessment, six populations from different states of Malaysia were selected, biotype labeled and their adults were bioassayed with five insecticides namely profenofos, cypermethrin, imidacloprid,diafenthiuron, and pymetrozine using leaf dip method. All populations for this study were Asia 1 biotype except Cameron Highlands which was Q biotype. The mortality was recorded and data were subjected to probit analysis to establish the median lethal concentration (LC50). The Q-type B. tabaci population from Cameron Highlands showed the highest level of resistance for all insecticides except cypermethrin. The lowest LC50 was 76.2 ppm of profenofos while the highest was 1631.9 ppm of diafenthiuron. The resistance ratio was then calculated based on the most susceptible population among all populations. Very high level of resistance that can compromise field efficacy was detected in population from Selangor against diafenthiuron (resistance ratio of 185) and population from Cameron Highlands against diafenthiuron (resistance ratio of 354.7) and pymetrozine (resistance ratio of 192.9). Identification of very high level of insecticide resistance especially in the Q biotype from Cameron Highlands necessitates modification of the current management approaches.